EMPOWERING THE HOUSEHOLD BUSINESS THROUGH IMPROVING THE QUALITY OF THE PRODUCT IN PINTUSONA SAMOSIR SUB-DISTRICT - Siahaan, Riana Friska; Saleh, Khaerul; Hanum, Yuspa (Universitas Negeri Medan, 2020)
This Community Service Program has been implemented well. Partners of this activity are Artiar Bakkery, Pintusona Village and Martauli Elisabet Household Business in Pinsona Village, Pangururan District, Samosir Regency, North Sumatra Province. The purpose of this PKM is to solve several problems faced by partners. In this service activity the implementation team tries to create a creative and innovative idea to provide added value to the cassava chip household business through improving product quality, namely by providing counseling and training on the application of science and technology. One of them is by changing the way of production by using modern equipment so that production capacity increases. Marketing of cassava chips with safe and attractive packaging so as to increase the selling price and expand the marketing area through online marketing. With this PKM activity it can improve partners' lives financially and partner products can be accepted in the market so that they can compete with similar products in the market.